STUDY OF THE ANTIMICROBIAL EFFECTS OF COMMERCIALLY AVAILABLE HERBAL TOOTHPASTES AGAINST EARLY CHILDHOOD CARIES - Faiz, Nadhirah; Geetha, RV; Mani, Geo; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
AIM: To determine whether herbal toothpastes have more antimicrobial effect than fluoridated toothpaste MATERIALS AND METHODS : 4 herbal toothpastes containing Neem, tulsi, ginger and aloe vera respectively were selected and 5 samples of saliva was collected from children between the age groups 4-5 years who had more than 5 teeth with caries present. Antimicrobial effect on these toothpastes were done having the control mediums of 0.2% chlorhexidine and fluoridated toothpaste using that saliva sample as well as isolated streptococcus mutants. The average zone of inhibition was calculated and analyzed. RESULT: Clove has been found to have better antimicrobial activity in comparison to the other herbal toothpastes and the controls. CONCLUSION: Herbal toothpastes contain good antimicrobial properties.